Twitter Followers Biased to Birth Times of Certain Celebrities - Oshop, Renay; Foss, Andrew (Journal of Scientific Exploration, 2015)
<!--[if gte mso 9]> <![endif]--> Astronomical relationships at the birth times of a subset of the top 1000 most popular Twitter users indicate that an ancient prediction for identifying strength in “followers” for the subset is indeed markedly likelier as the number of Twitter followers increases. Using publicly accessible data, it is shown that the incidence of this astronomical relationship at birth is higher amongst certain Twitter celebrities than expected by a Monte Carlo simulation, and that a strong positive correlation exists between those Twitter celebrities' follower numbers and this astronomical incidence in their birth charts. Within the top 500 Twitter users, the regression relation is similar, but even more acute. Finally, we confirm that Twitter ranking joins many other phenomena in Nature by following the Zipf-Mandelbrot law. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif";} --> <!--[endif] -->